Neutrophil and Platelet to Lmphocyte Ratio in Ovarian Malignancy - Francesca Utama; Hermie Tendean; Bismarck J Laihad (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To determine the sensitivity and specificity of neutrophil - lymphocyte ratio compared with platelet - lymphocyte ratio in predicting ovarian malignancies. Methods: This was an observational analytic study with diagnostic test design on 37 ovarian tumor patients who were planned to perform laparotomy in Prof. Dr. R.D. Kandou Hospital Manado and network hospitals in Manado from March to May 2016. We took blood samples to assess the complete blood count. Results: During the period, we obtained the mean age of 28.1 years old (range 18-71 years old). A total of 13 samples showed malignancy which the cystadenocarcinoma mucinosum (27.0%) as the most common histopathological types. Sensitivity and specificity value of neutrophil - lymphocyte ratio were 92.3% and 95.8% with 2.47 as the cut-off point. Meanwhile, the sensitivity and specificity of platelet - lymphocyte ratio were 61.5% and 75.0% with 152.86 as cut-off point. Conclusion: Both neutrophil - lymphocyte ratio and platelet - lymphocyte ratio are associated with ovarian malignancy. The sensitivity and specificity of neutrophil - platelet ratio show better prediction for ovarian malignancies. [Indones J Obstet Gynecol 2017; 5-1: 55-59] Keywords: neutrophil - lymphocyte ratio, ovarian cancer, platelet - lymphocyte ratio